PestDisPlace; Monitoring the distribution of pests and diseases. Version 1.0 - Cuéllar, Wilmer Jose; Mwanzia, Leroy; Lourido, Derlyn; García, Carolina; Cruz, Paola; Pino, Lizbeth; Tohme, Joseph M. (International Center for Tropical Agriculture, 2018)
A place to integrate and collectively monitor the occurrence and movement of pests and diseases. It is based on symptoms recording and confirmation by molecular diagnostics